ҲӘЗИРГИ ҚАРАҚАЛПАҚ ТИЛИНДЕ ПАРЦЕЛЛЯЦИЯ ҚУБЫЛЫСЫ ҲАҚҚЫНДА - Халмуратов, Т.Ж. (SCIENCE and SOCIETY, 2024)
The article is devoted to the study of parcelled constructions in the modern Karakalpak language.
Keywords: partcellation; sentence division; basic sentence; partcellator